2023
DOI: 10.1007/s10639-022-11517-3
|View full text |Cite
|
Sign up to set email alerts
|

Participation style and social anxiety as predictors of active participation in asynchronous discussion forums and academic achievement

Abstract: Learners in asynchronous discussion forums are inundated with diverse options when it comes to interaction. This enables the embodiment of various styles of participation. On the other hand, the affective domain tends to be overlooked in the online discussion context. The modeling of discussion activities based on both cognitive and affective indicators constitutes this study’s unique aspect. In the study, the impact of social anxiety and participation styles on active participation in discussions were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…More specifically, the country's (cultural) context appears to be a significant driver of social anxiety within the peer (student-to-student) interaction and student-to-instructor interaction (Zhong et al, 2007). As a reference to previous findings administering an identical instrument focussing on social anxiety levels among Turkish teacher education students, the lowest sub-scale in social anxiety has been somatic symptoms which corresponds with the findings of our present study (Demir et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More specifically, the country's (cultural) context appears to be a significant driver of social anxiety within the peer (student-to-student) interaction and student-to-instructor interaction (Zhong et al, 2007). As a reference to previous findings administering an identical instrument focussing on social anxiety levels among Turkish teacher education students, the lowest sub-scale in social anxiety has been somatic symptoms which corresponds with the findings of our present study (Demir et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, they recommend that there is a need for enhanced pedagogic support for students with social anxiety. A more recent study by Demir et al (2023) identified a significant impact of social anxiety among N = 272 Turkish pre-service teacher students on active participation in asynchronous discussions, which, in turn, significantly affected academic achievement. Claes et al (2023) examined the role of attentional control as a psychological factor involved in socioeconomic status-related social anxiety.…”
Section: Social Anxietymentioning
confidence: 99%
“…Through interactive discussions, students can reorganize their concepts, compare views with others, revise ideas, and develop previously unexplored thoughts (Liu & Yin, 2006). Several analytical models (e.g., Demir et al, 2023;Garrison et al, 2001;Gunawardena et al, 1997;Lai, 2015) have emerged in the past decades to explore the correlation between asynchronous online dialogues and the formation of novel knowledge (Nicholas & Ng, 2009) 1. sharing and comparing information, 2. discovering inconsistencies or conflicts, 3. negotiating meaning and proposing resolutions, 4. testing proposed ideas, and 5. reaching agreements, adopting newly constructed ideas or meta-cognitive reflection. The IAM posits that active knowledge construction moves through these five stages, with higher-level knowledge construction occurring from the second to the fifth stage (Hew and Cheung, 2011).…”
Section: Knowledge Construction In Asynchronous Online Discussion (Aod)mentioning
confidence: 99%
“…Through interactive discussions, students can reorganize their concepts, compare views with others, revise ideas, and develop previously unexplored thoughts (Liu & Yin, 2006). Several analytical models (e.g., Demir et al, 2023; Garrison et al, 2001; Gunawardena et al, 1997; Lai, 2015) have emerged in the past decades to explore the correlation between asynchronous online dialogues and the formation of novel knowledge (Nicholas & Ng, 2009). Gunawardena, Lowe, and Anderson's Interactive Analysis Model (IAM) and Garrison, Anderson, & Archer's (2001) Community of Inquiry (CoI) model are likely the two most commonly referenced and cited models.…”
Section: Literature Reviewmentioning
confidence: 99%